MODEL OF DEFORMATION OF FIBROUS MATERIALS OF MULTIDIRECTIONAL REINFORCEMENT WITH NONORIENTED FIBERS (Transport systems and technologies, 2021)
A model of deformation of multidirectional reinforcement fibrous materials with differently oriented fibers is proposed. The solution to the problem is built in two stages. At the first stage, the known properties of fibers and binder are used to determine the effective thermoelastic properties and stress-strain state of the subsystem with fibers oriented in a certain way relative to the main coordinate system. It is based on stochastic differential equations of the physically nonlinear theory of elasticity using the method of conditional moments. At the second stage, using a given distribution function based on the Voigt scheme, a model of deformation of the entire system is constructed from the calculated properties of the subsystems. Strain curves are obtained for simple loading, and the deformation of materials at uniform orientation of fibers is investigated. It was found that a fibrous composite material with differently oriented fibers in a macrovolume is isotropic, and its effective thermoelastic constants substantially depend on the volumetric content of fibers.
Keywords: fibrous material of multidirectional reinforcement, uniform orientation of fibers, stressstrain state, effective thermoelastic properties, computer implementation.